APPLICATION OF DIFFERENTIAL TRANSFORMATIONS FOR THE MODELING MOTION OF AEROSTATIC VEHICLES AND FOR THE SYNTHESIS OF CONTROL ALGORITHMS - Gusynin, A.V. (Proceedings of National Aviation University (archive), 2005)
The approach to simulation of flight dynamics and numerically-analytical method of airship control algorithms are offered. It’s based on differential transformations of initial mathematical model of airship motion. The given approach allows for elimination of viewing time function for their differential spectra in the image field. It gives the possibility to reduce a problem of closed algorithm synthesis of vehicle control to the solution of non-linear equation system concerning control variable.